Influencia de la inteligencia emocional en el comportamiento de las habilidades sociales en estudiantes universitarios. Riobamba, 2022. - Molina Cevallos, Dennis Sebastián (2022)
ABSTRACT: The current research entitled: "Influence of emotional intelligence in the behavior of social skills in university students. Riobamba, 2022". The objective was to analyze emotional intelligence and social skills in university students, through a field study, with a non-experimental cross-sectional design, with a correlational level. The population consisted of 567 university students of nursing and clinical psychology degrees, by means of simple random probability sampling, a sample of 327 participants was obtained. To obtain the results, the following psychological items were applied: Traid Meta-Mood Scale (TMMS-24) test of perceived intrapersonal emotional intelligence and Goldstein's social skills scale, whose data were processed using IBM SPSS-25 statistical software. The results obtained show that there is greater use of emotional intelligence in nursing students compared to clinical psychology students. With respect to social skills, there is a similarity in the level of use of most of its dimensions, except for the social skill related to feelings, where there is a predominance in clinical psychology students. To find the level of correlation, the Spearman coefficient was used, obtaining a result of the existence of a negative correlation between the dimension of emotional perception and the dimension of social skills related to feelings.